Enzymatic production of mono- and di- acylglycerols from Engkabang fat as halal food ingredients - Marikkar, Mohammed Nazrim; Nasyrah, A.R.; Mirghani, Mohamed Elwathig Saeed; Dzulkifly, M.H. (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
A study was carried out to compare the composition and thermal characteristics of mono- (MAG) and di-acylglycerol (DAG) from the seed fat of Shorea macrophylla known as Engkabang fat (EF) with those derived from cocoa butter (CB), palm (PO), rapeseed (RS) and sunflower (SF) oils. Solid-phase enzymatic glycerolysis of EF is found to yield 31.11% MAG and 27.78% DAG, which is comparable to the yield potential of CB. The fatty acid compositional patterns of MAG and DAG derived from these two fats is also comparably similar though not identical. Stearic is the most dominant fatty acid in both of them. This study suggests that enzymatic solid-phase glycerolysis of EF could be comparable to that of CB under the experimental condition adopted. Hence, EF could be a potential alternative raw material to CB for MAG and DAG preparation.